2021
DOI: 10.1007/s10479-021-04048-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing blockchain adoption barriers in manufacturing supply chains by the neutrosophic analytic hierarchy process

Abstract: Konstantinos (2021) Analyzing blockchain adoption barriers in manufacturing supply chains by the neutrosophic analytic hierarchy process. Annals of Operations Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 81 publications
1
44
0
2
Order By: Relevance
“…Since there are inadequate data regarding the loss of life, injury, and economic consequences, the current study has relied on experts’ experiences and knowledge to rank the causes of boiler accidents. To better interpret the opinion of experts, the current study has adopted neutrosophic AHP method that can provide reliable output under insufficient data ( Vafadarnikjoo et al., 2021 ; Darko et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since there are inadequate data regarding the loss of life, injury, and economic consequences, the current study has relied on experts’ experiences and knowledge to rank the causes of boiler accidents. To better interpret the opinion of experts, the current study has adopted neutrosophic AHP method that can provide reliable output under insufficient data ( Vafadarnikjoo et al., 2021 ; Darko et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Paul et al [29] found that blockchain has a significant positive effect on the tea supply chain and can effectively contribute to the global tea supply chain industry's sustainability. Vafadarnikjoo et al [30] proposed an action plan framework for identifying barriers to the implementation of blockchain technology based on the neutrosophic analytic hierarchy process (N-AHP). Yang et al [15] explored the values and impacts of blockchain on food supply chains with platform operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Business Owner's unwillingness: Fear of change, investment, organization culture [45,47] Unfamiliarity with Technology: Lack of awareness, the infancy of the technology [48,49] Data privacy/security Concerns: Cyber security concerns, possible illegal surveillance, and possible fear of data misuse [49,50] Technological infeasibility: Lack of enormous computing power, level of technical maturity is not the same along with the supply chain partners [41,42,51] Complexity in set up/use: Massive financial investment, common software platform required, initiators commitment [12,48,52,53] Uncertain benefits: Uncertain benefits are key practical challenges [54,55] Dependence on Blockchain operators: Trade-offs in the initial setup, fear of reliance on blockchain operators [56,57] Lack of Cooperation among SC partners: Supply chain partners must have the same level of technological maturity [58,59] Risks of cyber-attacks: Network-based attacks, Selfish mining attacks [60,61] Privacy Risks: Anonymity, Data Privacy with personal records [32,62] Market-based Risks: Price volatility and fluctuating exchange rate, Questionable hype, Risk of future adoption by merchants [41,63] Yadav and Singh [64] show the critical role of some of the causes that lead to the integration of blockchain with the supply chain and, ultimately, stability. Data security and decentralization, accessibility, rules and policies, documentation, data management and quality are some things that help block strategy development.…”
Section: Barrier and Description Referencementioning
confidence: 99%
“…The result of this paper has conflicted with some other researches. For instance, Vafadarnikjoo [49] uncertainty environment had the highest priority; however, it had fourth-order. This research has the same result as research Colak et al [71] and Bag et al [50] about the priority of barriers for implementation BC.…”
Section: Conclusion and Managerial Implementationmentioning
confidence: 99%